Higiene das mãos de profissionais de saúde em um hospital brasileiro: adesão, controle de infecção e transmissão de Staphylococcus aureus - Borges, Lizandra Ferreira de Almeida e (2009)
Health care-associated infection is a major cause of morbidity, mortality and increase costs in hospital and hands of health care workers are important reservoirs of nosocomial transmission of Staphylococcus aureus. Although hand hygiene remains as the method of simple and effective prevention, compliance to this practice is very low. Multimodal interventions in a strategy to promote hand hygiene are used successfully in developed countries, but information is scarce in Brazilian hospitals and developing countries. The aim of this study was to evaluate the impact of an intervention on hand hygiene in the prevalence of nosocomial infection and infection and colonization by S. aureus, or both, in a university hospital in Brazil, between February 2006 and July 2008. Hand hygiene compliance was assessed by direct observation and analyzed together with the prevalence of nosocomial infections, including infection or colonization by S. aureus resistant (MRSA) and susceptible to methicillin (MSSA), before and after an educational intervention, using posters, colored stickers, and feedback of results, in the wards of Internal Medicine, Surgery, Pediatrics, ICU adult and nursery high-risk (BAR) . Cultures of the hands of health care workers were conducted to verify their contamination by S. aureus. A total of 427 opportunities for hand hygiene was observed, with compliance of about 20% in units of care with adult patients, 24% in pediatric and 43% in neonatal, frequencies not varied in post-intervention, except in the BAR when hand hygiene compliance increased significantly, with 25% decrease in rates of nosocomial infection and 50% in colonization by MRSA. In assessing the contamination of the hands of health care workers was isolated 18% of S. aureus after the care of patients infected and colonized. The research showed a combination of high rates of nosocomial infection and poor compliance to hand hygiene, even after intervention, with the exception noted in the BAR. This failure could be due, in hospitals of developing countries, the shortage of human and financial resources, weak policies of hospital management and particularly with issues relating to education and motivation of the health care workers. However the success of the intervention occurred in the neonatal unit, where the participation of leadership was more evident is a hope of obtaining better results when the approach to such complex issues.